Modulation of Cilia Beat Kinematics Is a Key Determinant of Encounter Rate and Selectivity in Tintinnid Ciliates - Wandel, Hava; Holzman, Roi (Frontiers in Marine Science, 2022)
Tintinnids are a group of ciliated microzooplankton, who spontaneously settle on marine snow and other aggregates. Tintinnids create a feeding current that draws particles towards their mouth using a crown of continuously beating oral cilia. Similarly to other ciliated microzooplankton, not all encountered particles are ingested. However, it is unclear what is the mechanistic and behavioral basis of this selectivity. Here, we used particle tracking velocimetry to quantify the feeding flow, prey fate, and cilia beat frequency. We then asked (1) what determines the encounter rate with prey, (2) at which stages of the feeding sequence does selectivity develop, and (3) which predator’s behaviors modify selectivity. We found that the speed of the tintinnids’ feeding currents is modulated by their cilia beat frequency. Individual tintinnids were observed to modify their cilia beat frequency during foraging, resulting in ~3-fold acceleration or deceleration of the flow speed within seconds. Selectivity changed throughout the feeding sequence as tintinnids preferentially captured larger prey but subsequently preferentially ingested spherical over prolate prey. Short bouts of flow reversal mitigated the preference for larger prey during both encounter and handling. Overall, we show that individual tintinnids were able to modulate cilia kinematics, which affected encounter rates, encounter outcome, and handling outcome. The tintinnids’ ability to modulate their cilia kinematics is a major component of their feeding behavior.